Effect of Vasa Vasorum on Basilar Artery Vasospasm Following Subarachnoid Hemorrhage - Ozoner, Baris; Cakir, Tayfun; Kayaci, Selim; Aydin, Mehmet Dumlu; Aydin, Seckin; Demirci, Elif (Elsevier Science Inc, 2019)
BACKGROUND: A well-documented association exists between the vasa vasorum and vasopathologies, including atherosclerosis. However, information on the role of the vasa vasorum during vascular degenerative changes of vasospasm after subarachnoid hemorrhage (SAH) is insufficient. METHODS: In this study, 34 rabbits were divided into 3 groups: basal group (N = 8), sham group (N = 8), and SAH group (N = 18). Experimental SAH was formed using a double-injection model. During follow-up, the neurologic status of the rabbits was observed. All rabbits were euthanized after 2 weeks, and the vasopathologic degeneration was categorized as normal, mild, moderate, and severe according to the changes in the basilar arteries. The numbers, locations, and spasms of the vasa vasorum and their relation to the vasodegenerative changes of the basilar artery were investigated. RESULTS: The basilar arteries were graded as normal in the basal and sham groups. In the SAH group, 6 rabbits had mild, 7 had moderate, and 5 had severe degeneration. Neurologic deficits were prominent in the SAH group, and deficit grades correlated with vascular degeneration. The number of the vasa vasorum were significantly higher in the SAH group, and an enhanced formation of the vasa vasorum was noted in which severe degenerative changes were present. Moreover, the vasospasm index of the vasa vasorum, which increased with the aggravation of vascular degenerative changes, was significantly higher in the SAH group. CONCLUSIONS: The vasa vasorum and their vasospasm play a crucial role in the pathogenesis of basilar artery degeneration in the vasospasm following SAH.
Keywords: Basilar artery; Degeneration; Subarachnoid hemorrhage; Vasa vasorum; Vasospasm